Quercetin’s Effects on Glutamate Cytotoxicity - Kade Riche; Natalie R. Lenard (Molecules, 2022)
The potentially therapeutic effects of the naturally abundant plant flavonoid quercetin have been extensively studied. An extensive body of literature suggests that quercetin’s powerful antioxidant effects may relate to its ability to treat disease. Glutamate excitotoxicity occurs when a neuron is overstimulated by the neurotransmitter glutamate and causes dysregulation of intracellular calcium concentrations. Quercetin has been shown to be preventative against many forms of neuronal cell death resulting from glutamate excitotoxicity, such as oncosis, intrinsic apoptosis, mitochondrial permeability transition, ferroptosis, phagoptosis, lysosomal cell death, parthanatos, and death by reactive oxygen species (ROS)/reactive nitrogen species (RNS) generation. The clinical importance for the attenuation of glutamate excitotoxicity arises from the need to deter the continuous formation of tissue infarction caused by various neurological diseases, such as ischemic stroke, seizures, neurodegenerative diseases, and trauma. This review aims to summarize what is known concerning glutamate physiology and glutamate excitotoxic pathophysiology and provide further insight into quercetin’s potential to hinder neuronal death caused by cell death pathways activated by glutamate excitotoxicity. Quercetin’s bioavailability may limit its use clinically, however. Thus, future research into ways to increase its bioavailability are warranted.